INNOVATIVE ENTREPRENEURSHIP AS A FACTOR OF THE DEVELOPMENT OF THE PROCESSING INDUSTRY - VASIUTA, Viktoriia; ZHYTNYK, Oksana (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The development of modern innovative entrepreneurship is one of the main ways of Ukraine’s sustainable development. Innovations are a powerful tool that enhances its economic security and ensures competitiveness. Innovation is a driving factor in the development of both individual sectors of the economy and the entire economic system of any country. That is why the authors consider innovation as a factor in increasing the level of Ukraine’s competitiveness in the world market. The authors carried out a general assessment of the level of innovation in the domestic economy. The monitoring of the basic indicators of innovation was carried out based on a comparison of the positions of Ukraine and other European countries in world rankings, which characterizes innovative development. It was found that in 2021 Ukraine took 58th place in the Bloomberg Innovation Development Index. In 2022, it entered such rankings as the Global Innovation Index and the Networked Readiness Index, where it ranked 57 and 50, respectively. Ukraine lags far behind the advanced countries of Europe in the process of forming an innovative type of economic system. The authors found that the basis for ensuring the sustainable development of our state is the activity of processing industry enterprises. In recent years, the domestic processing industry brings about 10-11% of the total GDP. The authors note that it is advisable to define innovativeness as an extremely important and effective tool for improving the efficiency of the functioning of the business of the processing sector of the industry. The modern Ukrainian economy is characterized by the predominance of manufacturing enterprises with low-level technologies among the enterprises of the processing industry. For the period 2018-2020, the share of the number of innovatively active enterprises of the domestic processing industry was only 13.1%. However, despite the influence of various negative development factors, experts tend to believe that the development of innovative entrepreneurship in the processing industry, which will be based on the introduction of the latest innovative solutions in the production process, is important for the post-war recovery of Ukraine and strengthening its position in the world market.